On the numerical behavior of diffuse-interface methods for transcritical real-fluids simulations. (April 2019) - Ma, Peter C.; Wu, Hao; Banuti, Daniel T.; Ihme, Matthias
Highlights: Distinctly different mixing behaviors from different schemes are analyzed. Two limiting mixing models are identified. Theoretical analysis is confirmed with numerical simulation results. Available experimental data is utilized to assess different mixing models. Abstract: Accurate and robust simulations of transcritical real-fluid flows are crucial for many engineering applications. Diffuse-interface methods are frequently employed and several numerical schemes have been developed for simulating transcritical flows. These schemes can be categorized into two types, namely fully conservative (FC) and quasi-conservative (QC) schemes. In this study, numerical analysis is conducted to show that the mixing processes for isobaric systems follow the limiting cases of adiabatic and isochoric mixing models when FC and QC schemes are employed, respectively. It is shown that these distinct mixing behaviors are a consequence of numerical diffusion instead of physical diffusion, and can be attributed to insufficient spatial resolution. By considering several test cases, numerical simulations confirm these theoretical results. The analysis of experimental data suggests that the isochoric mixing provides better agreement in terms of the phase separation behavior. This analysis provides quantitative understanding on the interpretation of numerical simulation results and the mixing models that are commonly used to study transcritical flows.